SINTOMAS DE STRESS, ANSIEDADE E DEPRESSÃO EM UNIVERSITÁRIOS DE CURSOS DE SAÚDE - LUZ, FABÍOLA MORATTI (2017)
Mental diseases such as depression and anxiety, along with the stress, are present in great part of the world’s population, among individuals of many ages and they provoke important social and economic damages to the public health, besides the human suffering. University students have shown themselves susceptible and vulnerable, due to various factors that influence the health and wellness of these young students. This way, the present study had as an objective: a. Identify the presence of stress and symptoms of anxiety and depression among university students from health areas from a private university; b. Collect and describe sociodemographic data from this sample of university students; c. Relate sociodemographic data, genre and course option chosen with the stress variables, anxiety and depression. 157 university students from the health area have participated in the study, from an university located in the metropolitan region of São Paulo, with average age of 23,7. For the data collection, some tolls were used: sociodemographic data questionnaire and DASS-21- Depression, Anxiety and Stress Scale, applied in classrooms. The dada was analyzed by descriptive statistics [average and standard deviation], ANOVA, Post Hoc test (Tukey) and the Student t test. The results have indicated a sample composed mostly by women (84,1%), single (91%). The variable stress has been present in all students, 61,1% present some level of stress. The variable depression has reached 42,6% and the anxiety 46,5% among students. The students from the pharmacy course have presented the highest scores for the three studied variables and the psychology students have presented the lowest scores. Besides being present in different levels, it was verified the association among depression, anxiety and stress. It was concluded by the importance of support to the implementation of actions in health that help the prevention, precocious diagnosis, as well as the psychological treatment of university students